Bio-milling technique for the size reduction of chemically synthesized BiMnO3 nanoplates - Mazumder, Baishakhi; Uddin, Imran; Khan, Shadab; Ravi, Venkat; Selvraj, Kaliaperumal; Poddar, Pankaj; Ahmad, Absar (Journal of Materials Chemistry, 2007)
Wet- chemical techniques for the synthesis of complex oxide materials have advanced significantly; however, achieving finely dispersed nanoparticles with sizes less than 10 nm still remains challenging, especially for the perovskite family of compounds. On the other hand, a fungusmediated synthesis technique has recently shown potential to synthesize perovskites such as BaTiO3 with sizes as small as 5 nm. Here we report, for the first time, the use of fungal biomass, at room temperature, to break down chemically synthesized BiMnO3 nanoplates ( size similar to 150 - 200 nm) into very small particles (, 10 nm) while maintaining their crystalline structure and the phase purity. This novel technique that we have named as `` bio- milling'' holds immense potential for synergically utilizing both chemical and biological synthesis techniques to synthesize complex oxide nanoparticles with particle sizes less than 10 nm with the proper crystalline phase.

Fungus-based synthesis of chemically difficult-to-synthesize multifunctional nanoparticles of CuAlO2 - Ahmad, Absar; Jagadale, Tushar C.; Dhas, Vivek V.; Khan, Shadab; Patil, Shankar; Pasricha, Renu; Ravi, Venkat; Ogale, Satishchandra B. (Advanced Materials, 2007)
Fungal nanosynthesis of ternary CuAlO2 phase is achieved at 50 degrees C. This phase is chemically difficult to synthesize at low temperatures because of the incompatible oxidation chemistry of Cu and Al. The synthesized protein-capped water-dispersible nanoparticles show blue luminescence and radio-frequency absorption (see figure).

Extracellular biosynthesis of metal sulfide nanoparticles using the fungus fusarium oxysporum - Senapati, Satyajyoti; Syed, Asad; Khan, Shadab; Pasricha, Renu; Khan, Mohammad Islam; Kumar, Rajiv; Ahmad, Absar (Current Nanoscience, 2014)
The development of reliable, eco-friendly processes for the synthesis of nanomaterials is an important aspect of nanotechnology. One approach that shows immense potential is based on the biosynthesis of nanoparticles using microorganisms such as bacteria. In this report, we demonstrate the extracellular biosynthesis and complete characterization of metal sulfide (PbS, ZnS, MnS and NiS) nanoparticles using fungus, Fusarium oxysporum. We observed that the exposure of aqueous solution of 1 mM metal sulfate to fungus Fusarium oxysporum resulted in the formation of highly stable technologically important metal sulfide semiconductor nanoparticles. Fusarium oxysporum synthesizes lead sulfide and zinc sulfide nanoparticles of fractal type structure whereas manganese sulfide and nickel sulfide nanoparticles are of variable polydispersed morphology. The variable morphology may be due to the dissimilar interaction of metal sulfide nanoparticles with capping proteins secreted by the fungus in solution. The nanoparticles solution is found to be extremely stable with little evidence of aggregation even after a month of storage. The long term stability of the nanoparticles is due to the proteins secreted by fungus in the nanoparticle solution which bind to the surface of the nanoparticles and thus prevent aggregation.
Keywords: Biosynthesis; enzymes; fungi; metal sulfide; Nanoparticles

Biosynthesis of anti-proliferative gold using endophytic fusarium oxysporum strain isolated from neem (A-indica) leaves - Siddiqui, Ejaz Ahmad; Ahmad, Absar; Julius, Anju; Syed, Asad; Khan, Shadab; Kharat, Mahesh; Pai, Kalpana; Kadoo, Narendra Y.; Gupta, Vidya (Current topics in medicinal chemistry, 2016)
Here we report a simple, rapid, environment friendly approach for the synthesis of gold nanoparticles using neem (Azadirachta indica A. Juss.) fungal endophyte, which based upon morphological and cultural characteristics was eventually identified as Fusarium oxysporum. The aqueous precursor (HAuCl4) solution when reacted with endophytic fungus resulted in the biosynthesis of abundant amounts of well dispersed gold nanoparticles of 10-40 nm with an average size of 22nm. These biosynthesized gold nanoparticles were then characterized by standard analytical techniques such as UV-Visible spectroscopy, X-ray diffraction, Transmission Electron Microscopy and Fourier Transform Infrared Spectroscopy. Cytotoxic activity of these nanoparticles was checked against three different cell types including breast cancer (ZR-75-1), Daudi (Human Burkitt's lymphoma cancer) and normal human peripheral blood mononuclear cells (PBMC), where it was found that our gold nanoparticles are anti-proliferative against cancer cells but completely safe toward normal cells. In addition to this, assessment of toxicity toward human RBC revealed less than 0.1 % hemolysis as compared to Triton X-100 suggesting safe nature of our biosynthesized gold nanoparticles on human cells. Also, our nanoparticles exhibited no anti-fungal (against Aspergillus niger) or anti-bacterial [against Gram positive (Bacillus subtilis & Staphylococcus aureus) and Gram negative (Escherichia coli & Pseudomonas aeruginosa) bacteria] activity thus suggesting their non-toxic, biocompatible nature. The present investigation opens up avenues for eco-friendly, biocompatible nanomaterials to be used in a wide variety of application such as drug delivery, therapeutics, theranostics and so on.

Size reduction of bulk alumina for mass production of fluorescent nanoalumina by fungus humicola sp. - Moeez, Sana; Siddiqui, Ejaz Ahmad; Khan, Shadab; Ahmad, Absar (Journal of Cluster Science, 2017)
In recent years, nanomaterials have made their way into hundreds of biomedical, life-sciences and technological applications. One such nanomaterial of extreme importance is nanoalumina (Al2O3 nanoparticles). This nanomaterial is an epitome of diversity with applications exhibited in the fields of catalysis, cosmetics, theranostics, energy generation, biosensors, drug-delivery, tumor-regression, etc. However, problems persist in terms of biocompatibility, cost-effectiveness, reproducibility and mass-production of nanoalumina by the presently existent physical, chemical and biological methodologies. Herein, we for the first time are presenting a top-down biofabrication method by which size reduction of commercial bulk alumina/aluminum oxide (5 A mu m) into nanoalumina (5-25 nm) is carried out by a thermophilic fungus Humicola sp. within 96 h of reaction at just 50 A degrees C. The so-formed nanoalumina is highly stable, water dispersible, fluorescent and natural protein capped; characterization engaged standard techniques. These nanoparticles exhibit anti-bacterial properties against Gram-positive Bacillus subtilis strain and may serve as broad spectrum bactericidal agents. We believe that our novel top-down approach may be extensively used in the facile, inexpensive, eco-friendly and reliable fabrication of abundant quantities of nanomaterials of different chemical compositions, sizes and shapes with better control and predictability over the properties as derived from their substrates. The mechanistic aspect of said protocol is underway.